Інтеграція нейронних мереж у медичні пристрої на основі STM32 для автоматичної діагностики та моніторингу пацієнтів - Чумак, В. С. (ХНУРЕ, 2023)
This article discusses the technical aspects of integrating neural networks into medical devices based on STM32 microcontrollers. The focus is on the selection and optimization of communication interfaces, the development of software for interacting with neural networks, and the implementation of machine learning algorithms. Technical analysis includes memory management, code optimization, and the use of development tools. Overcoming challenges associated with limited resources ensures the creation of intelligent medical devices with increased diagnostic accuracy and efficiency.
Keywords: догляд персоналізований; STM32; нейронна мережа